PELUANG DAN TANTANGAN DEEP LEARNING DALAM PENDIDIKAN - Salilah, Nur; Musyarofi, Ahmad; Aziz, Fidyah Aliati; Rifqiya, Azma Aulia; Hakim, Alif Rahman; Suhardi, Suhardi (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This article analyzes the opportunities and challenges of implementing deep learning as a transformative approach in education. In the digital era, deep learning emerges as a response to the need for 21st-century skills. This approach aims to shift the traditional educational paradigm from one focused on rote memorization to the development of competencies such as critical thinking, creativity, and collaboration. The research method used is a literature review with a qualitative descriptive approach, examining various relevant literatures.The research results indicate opportunities, including the potential to create personalized and adaptive learning tailored to each student's needs and to increase active learning engagement. However, its implementation faces challenges such as wide technological infrastructure gaps, especially in remote areas; inadequate digital competence among teachers; ethical risks related to student data privacy and security; and an organizational culture in schools that is resistant to change. It is concluded that the successful integration of deep learning requires a comprehensive and collaborative national strategy. This strategy must include curriculum reform, equitable access to infrastructure, continuous teacher capacity-building programs, and the strengthening of secure and ethical data governance to realize an adaptive and inclusive education system for all.